RENAL CORTICAL NECROSIS: A CASE SERIES OF NINE PATIENTS & REVIEW OF LITERATURE - Ali, Syed Sohail; Rizvi, Syed Zulfiqar Hyder; Muzaffar, Suhail; Ahmad, Aasim; Ali, Akhtar; Hassan, Sheema H. (Journal of Ayub Medical College Abbottabad, 2003)
Background: The purpose of this study is to review cases of renal cortical necrosis (RCN) which we came across during a period of five years, confirmed on needle biopsy specimens, with literature available so far. Methods: All renal biopsy records between January 1996 to December 2001 at the Aga Khan University Hospital, Karachi, Pakistan were reviewed to identify patients with histologically proven renal cortical necrosis. Seven patients were also referred by the department of Nephrology, Lady Reading Hospital, Peshawar, Pakistan. Patients' medical records were reviewed for demographic, clinical, and follow up data. Results: There were total of nine patients identified with renal cortical necrosis. The mean age was 26.21±13.01 year. Five cases (55.5%) were caused by obstetric complications. The most common histology type of RCN was patchy cortical necrosis in seven patients (77.8%). Three patients were alive at last follow up; remaining patients were lost to follow up. Conclusion: Obstetric complications remain the leading cause of renal cortical necrosis in our setting. The recognition of this entity and value of renal biopsy in cases of acute renal failure needs to be emphasized as this helps in establishing diagnosis, to assess prognosis and to aid in selection of a rational approach to therapy. KEY WORDS: Renal cortical necrosis, renal biopsy, acute renal failure.